The protein kinase A catalytic subunit Cβ2: molecular characterization and distribution of the splice variant. - Thullner, Sandra; Wiemann, Stefan; Pyerin, Walter; Kinzel, Volker; Bossemeyer, Dirk (Biochemical journal, 2000)
Cbeta2, a 46 kDa splice variant of the Cbeta isoform, is the largest isoform so far described for catalytic subunits from cAMP-dependent protein kinase in mammals. It differs from Cbeta in the first 15 N-terminal residues which are replaced with a 62-residue domain with no similarity to other known proteins. The Cbeta2 protein was identified in cardiac tissue by MS, microsequencing and C-subunit-isoform-selective antibodies. The Cbeta2 protein has a very low abundance of about 2% of total affinity-purified C subunits from bovine cardiac tissue. This, and the similarity of its biochemical properties to Calpha and Cbeta, are probably some of the reasons why the Cbeta2 protein has escaped detection so far. The abundance of the Cbeta2 protein differs dramatically between tissues, with most protein detected in heart, liver and spleen, and the lowest level in testis. Cbeta2 protein shows kinase activity against synthetic substrates, and is inhibited by the protein kinase inhibitor peptide PKI(5-24). The degree of Cbeta2 removal from tissue extracts by binding to PKI(5-24) depends on the cAMP level, i.e. on the dissociation state of the holoenzyme. Two sites in the protein are phosphorylated: Thr-244 in the activation segment and Ser-385 close to the C-terminus. By affinity purification and immunodetection Cbeta2 was found in cattle, pig, rat, mouse and turkey tissue and in HeLa cells. In the cAMP-insensitive CHO 10260 cell line, which has normal Cbeta but is depleted of Calpha, stable transfection with Cbeta2 restored most of the cAMP-induced morphological changes. Cbeta2 is a ubiquitously expressed protein with characteristic properties of a cAMP-dependent protein kinase catalytic subunit.
Gesehen am 23.02.2021
DOI fehlerhaft